Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Direktorat XYZ - Muhammad Hasbi Gurumindah; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine the influence of motivation and work environment on employee performance at the Directorate General of Military Justice and State Administration, partially or simultaneously. The method used is a quantitative method. The research was conducted from April to June with the research objects being employees of the Directorate General of Military Justice and State Administration, totaling 75 respondents. The data analysis techniques used are Data Quality Test, Classical Assumption Test, Hypothesis Test, Multiple Regression Analysis, Determination Coefficient Test using the IBM SPSS 25 application. The results of this research show that partially motivation has a positive and significant influence on employee performance. This is shown based on the sig results of 0.032 < 0.05 and t count > t table 2.185 > 1.666 and partially the work environment has a positive and significant effect on employee performance. This is proven by the results of the sig value of 0.000 < 0.05 and t count > t table 3,719 > 1.666. Meanwhile, based on the results of the F Test, motivation and work environment have a positive and significant influence on employee performance. This is proven by the results of a sig value of 0.000 < 0.05 and a calculated F value > F table of 10.313 > 3.124.